Citizen Democracy Studies: A Systematic Literature Review - Ananta, Ataya Qonita; Salahudin, Salahudin; Firdaus, Muhammad (FISIP Universitas Malikussaleh, 2024)
This research aims to find out how democratic citizens develop in the world. The research method applied to this research is a systematic review of literature using 140 scientific articles derived from scope databases. Reviewing articles using the Vosviewer application. The results reveal the concept of the dominance of citizen participation and democratic freedom. But in global democracy, many countries lack democratic principles, leading to erosion and autocracy. Democracy affects public policy through legislative branches, including representative democracy, which affects national security and social justice. In addition, it was found that per analysis of research data carried out from 2022 to 2023 related to the concept of civil democracy in some countries has an upward trend, as the volume of discussion on this topic continues to increase every year. Research results have contributed to the development of research on civil democracy in the world. The limitation of this research is that articles are only used from scope databases so the research findings cannot comprehensively describe issues of citizen democracy. Further research needs to use scientific articles derived from other leading international datasets, such as the Web of Science and Dimensionds Scholars.